IMPACT OF BEETROOT (BETA VULGARIS RUBRA) AND/OR SWISS CHARD (BETA VULGARIS CICLA) JUICES ORAL ADMINISTRATION AGAINST BARIUM CHLORIDE-INDUCED HYPOKALEMIA, ATPASE DISTURBANCE HEART AND LUNG TOXICITY IN RATS - S GABAL, ALYAE M; M MORSY, GEHAN (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The research designed to explore, for the 1st time, the probable antioxidant activity and protective effect of oral administration of beetroot (Beta vulgaris Rubra) and Swiss chard (B. vulgaris Cicla) juices against barium chloride (BaCl2)-induced toxicity in rats through investigating the changes on complete blood picture, heart and lung oxidative biomarkers, cardiac function tests, inflammatory markers as well as adenosine triphosphatase (ATPase) activity, hypokalemia, and electrolyte disturbances. Methods: Seventy-five adult male albino rats of Sprague-Dawley strains (150±5 g) were divided into five groups (15/each) except healthy control group which contains 10 rats, and BaCl2 control group that contains 20 rats as follows: Group I: Healthy control; Group II: BaCl2 control, and Groups III, IV, and V: BaCl2 intoxicated groups supplemented with 1 ml of beetroot, Swiss chard, and combination of both juices, respectively/kg body weight 3 times per week orally. Results: Results explored that beetroot and Swiss chard juices contain significant amount of polyphenols and flavonoids as well as macro- and micronutrients that improved the complete blood picture, heart and lung oxidative stress parameters, cardiac function tests, inflammatory markers, ATPase activity, hypokalemia, and also electrolyte balance in supplemented groups compared to BaCl2 control group. Conclusion: This search illustrated that fresh beetroot and Swiss chard juices can improve various biochemical abnormalities resulted from BaCl2 toxicity. BaCl2 intoxicated rats that were supplemented with combination of juices showed the most significant improvements.